Pemanfaatan Aplikasi GoodNovel dalam Peningkatan Apresiasi Sastra dan Literasi Digital Siswa SMK Paskita Global - Latiah, Ummi; Prawono, Shella Wati; Prawono, Shelly Yuliani; Pitriyani, Dea; Wahyuningrum, Alfani Dwi; Megawati, Erna; Patturahman, Maman; Nugraha, Santi (CV Buana Prisma Sejahtera, 2023)
Digital literacy writing literary novels through the GoodNovel application. GoodNovel is a global original fiction platform dedicated to producing the latest generation of